Pemaduan Pseudomonas putida 27.4B dan Trichorderma sp. dalam Media Cair Senyawa Humik yang Diberi Zeolit untuk Mendapatkan Produk Multifungsi Ramah Lingkungan - Sugeng WINARSO; Eko HANDAYANTO; SYEKHFANI .; Didik SULISTYANTO (Fakultas Pertanian Universitas Jember, 2008)
Phosphate solubilizing bacteria (Pseudomonas putida 27.4B) is effective in dissolving undissolve P;humik compound can decrease Al exchange in acid soil and can be used as microorganism liquidmedia; Zeolite can improve CEC and bases concentration; and Trichorderma sp. can control diseaseand increase crop yield. Therefore, aim of this research is to make product having multifunction bothenvironment friendly soil amandement (fertilizer) and biopesticide, combination Pseudomonas putida27.4B, humic compound, zeolite, and Trichorderma sp.Potetoes Dextro Agar (PDA) media used to see resistance and growth, continued humic compoundliquid media added zeolite. Research design is completele randomized design with three factor are: 1)Trichorderma sp. concentration are: 0 (control); 104 CFU.ml-1; 105 CFU.ml-1; dan 106 CFU.ml-1; 2)good combination obtained last research are: a). 1000 ppm humic compound; 0,1% zeolit; P. putida27.4B 1012 CFU.ml-1 and b). 5000 ppm humic compound; 0,1% zeolit; P. putida 27.4B 1012 CFU.ml-1; and 3) incubation time are: 2 and 4 weeks.Result of research indicate that combination Pseudomonas putida 27.4B and Trichorderma sp. inPDA media can grow together, with visually speed of Trichorderma sp. growth faster thanPseudomonas putida 27.4B. Pseudomonas putida 27.4B proven can live on, even very good, in humiccompound liquid media added zeolite and Trichorderma sp. Its best growth is at humic compoundconcentration 1000 ppm. Besides that is tendency of combination Pseudomonas putida 27.4B andTrichorderma sp. exactly can increase growth of Pseudomonas putida 27.4B both at humic compoundconcentration 1000 ppm and without addition of humic compound. While at humic compoundconcentration 5000 ppm, Trichorderma sp. inokulasi exactly decrease Pseudomonas putida 27.4B.